Toxoplasma gondii CDPK3 Controls the Intracellular Proliferation of Parasites in Macrophages - Wu, Minmin; An, Ran; Zhou, Nan; Chen, Ying; Cai, Haijian; Yan, Qi; Wang, Ru; Luo, Qingli; Yu, Li; Chen, Lijian; Du, Jian (Frontiers in Immunology, 2022)
Interferon-γ (IFN-γ)-activated macrophages restrain the replication of intracellular parasites and disrupt the integrity of vacuolar pathogens. The growth of the less virulent type II strain of Toxoplasma gondii (such as ME49) was strongly inhibited by IFN-γ-activated murine macrophages. However, the mechanism of resistance is poorly understood. Immunity-related GTPases (IRGs) as well as guanylate-binding proteins (GBPs) contributed to this antiparasitic effect. Previous studies showed the cassette of autophagy-related proteins including Atg7, Atg3, and Atg12-Atg5-Atg16L1 complex, plays crucial roles in the proper targeting of IFN-γ effectors onto the parasitophorous vacuole (PV) membrane of Toxoplasma and subsequent control of parasites. TgCDPK3 is a calcium dependent protein kinase, located on the parasite periphery, plays a crucial role in parasite egress. Herein, we show that the less virulent strain CDPK3 (ME49, type II) can enhance autophagy activation and interacts with host autophagy proteins Atg3 and Atg5. Infection with CDPK3-deficient ME49 strain resulted in decreased localization of IRGs and GBPs around PV membrane. In vitro proliferation and plaque assays showed that CDPK3-deficient ME49 strain replicated significantly more quickly than wild-type parasites. These data suggested that TgCDPK3 interacts with the host Atg3 and Atg5 to promote the localization of IRGs and GBPs around PV membrane and inhibits the intracellular proliferation of parasites, which is beneficial to the less virulent strain of Toxoplasma gondii long-term latency in host cells.